The Aedes albopictus (Diptera: Culicidae) microbiome varies spatially and with Ascogregarine infection. - Priscilla Seabourn; Helen Spafford; Nicole Yoneishi; Matthew Medeiros (Public Library of Science (PLoS), 2020)
The mosquito microbiome alters the physiological traits of medically important mosquitoes, which can scale to impact how mosquito populations sustain disease transmission. The mosquito microbiome varies significantly within individual mosquitoes and among populations, however the ecological and environmental factors that contribute to this variation are poorly understood. To further understand the factors that influence variation and diversity of the mosquito microbiome, we conducted a survey of the bacterial microbiome in the medically important mosquito, Aedes albopictus, on the high Pacific island of Maui, Hawai'i. We detected three bacterial Phyla and twelve bacterial families: Proteobacteria, Acitinobacteria, and Firmicutes; and Anaplasmataceae, Acetobacteraceae, Enterobacteriaceae, Burkholderiaceae, Xanthobacteraceae, Pseudomonadaceae, Streptomycetaceae, Staphylococcaceae, Xanthomonadaceae, Beijerinckiaceae, Rhizobiaceae, and Sphingomonadaceae. The Ae. albopictus bacterial microbiota varied among geographic locations, but temperature and rainfall were uncorrelated with this spatial variation. Infection status with an ampicomplexan pathosymbiont Ascogregarina taiwanensis was significantly associated with the composition of the Ae. albopictus bacteriome. The bacteriomes of mosquitoes with an A. taiwanensis infection were more likely to include several bacterial symbionts, including the most abundant lineage of Wolbachia sp. Other symbionts like Asaia sp. and several Enterobacteriaceae lineages were less prevalent in A. taiwanensis-infected mosquitoes. This highlights the possibility that inter- and intra-domain interactions may structure the Ae. albopictus microbiome.